2018
DOI: 10.1039/c8ra02615g
|View full text |Cite
|
Sign up to set email alerts
|

Mg-promotion of Ni natural clay-supported catalysts for dry reforming of methane

Abstract: Mg-promotion of natural clay based Ni-catalysts was considered, as a way of boosting the dry reforming of methane (DRM) activity of these materials. The results of the DRM experiments performed at temperatures from 600 C to 850 C evidenced much higher methane and CO 2 conversions for the Mg-promoted catalysts. Mg-promotion led of course to a significant increase of CO 2 -adsorption ability (basicity).However, the increased catalytic activity of the Mg-promoted materials was rather linked to increasedNi-dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In the scenario of a TPR profile, the results of all catalysts presented a main area of interest in which several H 2 -consumption peaks can be observed in the temperature range of 500 to 700 °C. It means that the H 2 reduction of finely dispersed NiO x and/or Ni-species is in tight interaction with the catalyst support . The H 2 consumption of the produced 100CF-10NAM/PU catalyst with 5 °C/min of heating rate was obviously predominant compared to the rest of the catalysts (Figure ).…”
Section: Resultsmentioning
confidence: 71%
“…In the scenario of a TPR profile, the results of all catalysts presented a main area of interest in which several H 2 -consumption peaks can be observed in the temperature range of 500 to 700 °C. It means that the H 2 reduction of finely dispersed NiO x and/or Ni-species is in tight interaction with the catalyst support . The H 2 consumption of the produced 100CF-10NAM/PU catalyst with 5 °C/min of heating rate was obviously predominant compared to the rest of the catalysts (Figure ).…”
Section: Resultsmentioning
confidence: 71%
“…[50] However, the relatively short time for the ammonium vapour treatment of this method (the 10Ni (12T)/MA catalyst) can cause too strong adsorption of CO 2 during the CRM process because of the large number of the strong basic sites. [54] CRM tests over the 10Ni(xT)/MA catalysts at 620 C for 6 hours under ambient pressure were conducted to find the suitable 10Ni(xT)/MA catalyst for the CRM process. The catalytic performance was determined based on CH 4 and CO 2 conversions as well as the generated H 2 /CO ratio (Figure 7A-C).…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that the strong basic sites result in far too tight adsorption of CO 2 and thus its limited reaction with CH 4 . [54] Therefore, the catalyst should be treated in the ammonium vapour until the Ni nanosheets are formed to avoid a large number of strong basic sites. Furthermore, all 10Ni(xT)/MA catalysts produced a H 2 /CO ratio of approximately 0.9, which was ascribed to a less reverse water gas shift due to the basicity of the 10Ni(xT)/MA catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Doping a promoter element is a common way to modify the Ni catalysts to improve the carbon resistance. It was found that the dopant of noble metals like Pt or Rh could alleviate the carbon deposition and decrease the deactivation rate, but cannot prevent the deactivation completely. Alkali metal dopants like K could decrease the carbon deposition, whereas alkaline earth metal dopants like Mg would increase the deposition of carbon over Ni catalysts . As for other transition metals or the main-group metals, most of them show improved carbon resistance, , but some of them show no improvement in carbon resistance or activity.…”
Section: Introductionmentioning
confidence: 99%
“…17−21 Alkali metal dopants like K could decrease the carbon deposition, 22 whereas alkaline earth metal dopants like Mg would increase the deposition of carbon over Ni catalysts. 23 As for other transition metals or the main-group metals, 24−26 most of them show improved carbon resistance, 24,25 but some of them show no improvement in carbon resistance or activity. For example, Zhu and co-workers found that the activity of the Ni/Al 2 O 3 catalyst was not improved upon the doping of Mg, and the carbon deposition even became more severe than that on the unmodified Ni/Al 2 O 3 catalyst.…”
Section: Introductionmentioning
confidence: 99%